Sickle cell disease: a case report of renal amyloidosis - Bugeja, Ann; Blanco, Paula; Clark, Edward G; Sood, Manish M (Université d'Ottawa | University of Ottawa, 2018)
Abstract Background The development of proteinuria and reduced glomerular filtration rate is associated with higher mortality among patients with sickle cell disease (SCD). AA amyloidosis, also associated with increased mortality, in SCD is rare. We present a case of a woman with homozygous sickle cell disease with nephrotic syndrome and antibodies to double stranded DNA without clinical features of systemic lupus erythematosus. Kidney biopsy reveals AA amyloidosis and is the first report of concomitant AA amyloidosis with antibodies to double stranded DNA in SCD. Case presentation A 40-year-old Central African woman with homozygous sickle cell disease and history of vaso-occlusive pain crises undergoes kidney biopsy for nephrotic-range proteinuria. Kidney biopsy reveals AA type amyloidosis, which is a rare manifestation of SCD in the kidney. Her anemia worsens with an ACE inhibitor, initiated to reduce proteinuria and limit GFR decline, so it was discontinued. Hydroxyurea, shown to decrease the frequency of vaso-occlusive crises and lower proteinuria, was subsequently initiated but then discontinued due to worsening anemia. Unfortunately, her glomerular filtration rate worsens. Conclusions AA amyloidosis and antibodies to double stranded DNA can occur in sickle cell disease. ACE inhibition and hydroxyurea decrease proteinuria so they may limit progression of chronic kidney disease. Hydroxyurea also decreases frequency of vaso-occlusive pain crises so it might be helpful in limiting progression of renal AA amyloidosis. However, further studies are needed to determine optimal treatment strategies for AA amyloidosis in sickle cell disease.